EXPERIMENTAL INVESTIGATION ON COMBUSTION CHARACTERISTICS OF REFINE CORN OIL WITH ARECA CATECHU EXTRACT AS ADDITIVE - Wardoyo, Wardoyo; Widodo, Agung S.; Wijayanti, Widya; Wardana, I. N. G. (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2020)
The need for vegetable oils as alternative energy reserves increases with the depletion of fossil energy sources. Vegetable oil is the strongest candidate to replace the fossil energy. However, the use of vegetable oil directly as fuel is limited by high viscosity. Viscosity like this results in non-ideal atomization, challenging to evaporate, and cannot burn completely. Among the methods that have been studied by previous researchers and which have proven to be effective, cheaper, and can reduce the viscosity of vegetable oils better is the mixing method. In this study, corn oil was mixed with areca extract as an additive. Areca extract contains polyphenols which are polar types of epicatechin. Epicatechin has three aromatic rings and several hydroxyl groups. Delocalisation of electrons in aromatic rings can produce London forces on vegetable oil molecules, thereby increasing the reactivity of burning vegetable oil droplets. The burning characteristics of corn vegetable oil affected by areca extract have been studied experimentally at room temperature and atmospheric pressure. The results showed that the rate and temperature of combustion increased, as well as the presence of micro explosions. The London force that appears causes the bonds in the triglyceride molecules to weaken so that the combustion becomes reactive, the rate of heat transfer in the droplets gets better, facilitates the appearance of micro explosions and increases the combustion temperature. Vegetable oil from corn has been studied experimentally at atmospheric pressure and room temperature. The results show an increase in the rate of combustion, an increase in combustion temperature, and the presence of micro explosions. London force that appears causes the bonds in the triglyceride molecules to weaken so that combustion becomes more reactive, the rate of heat transfer in the droplet gets better, facilitates the appearance of micro explosions and raises the combustion temperature.